Development of an exercise intervention to improve cognition in people with mild to moderate dementia: Dementia And Physical Activity (DAPA) Trial, registration ISRCTN32612072. Issue 2 (June 2015) - Brown, Deborah; Spanjers, Katie; Atherton, Nicky; Lowe, Janet; Stonehewer, Louisa; Bridle, Chris; Sheehan, Bart; Lamb, Sarah E.
Abstract: More than 800 000 people in the UK have dementia, and it is a government priority to improve dementia care. Drug treatment options are relatively limited. The Dementia And Physical Activity (DAPA) study is a randomised trial which targets cognition in people with dementia, using an exercise programme. There is evidence to suggest that both aerobic and resistance exercise may be useful in improving cognition. Hence the intervention comprises a supervised part of twice-weekly exercise classes of one hour duration for 4 months, including aerobic exercise at moderate intensity on static bicycles, and resistance (weight training) exercise using weight vests, weight belts and dumbbells. Thereafter participants progress to unsupervised, independent exercise. Aids to behaviour modification have been incorporated into the intervention. The DAPA intervention has been designed to maximise likelihood of effectiveness and cost-effectiveness, and for delivery in the UK National Health Service.